INFORMAL VOCABULARIES IN INDONESIAN - I Dewa Putu Wijana (Sirok Bastra, 2022)
This research concerns about the Indonesian informal vocabularies compared to their formal equivalents regarding their forms and semantic characteristics. Using data collected from Indonesian Big Dictionary, it is found that in spite of vocabularies which are specifically used for serving informal speech styles, there are also ones that are modified from their formal counterparts through various phonological processes, such as deletion, addition, and substitution. Meanwhile, with regard to their socio-semantic characteristics, the informal vocabularies can be foreign, local, and polysemic (secondary meaning, onomatopoeic, and slangy) variation of their formal equivalents.